Circadian Disruption Changes Gut Microbiome Taxa and Functional Gene Composition - Deaver, Jessica A.; Eum, Sung Y.; Toborek, Michal (Frontiers in Microbiology, 2018)
Disrupted circadian rhythms and alterations of the gut microbiome composition were proposed to affect host health. Therefore, the aim of this research was to identify whether these events are connected and if circadian rhythm disruption by abnormal light-dark cycles affects microbial community gene expression and host vulnerability to intestinal dysfunction. Mice were subjected to either a four-week period of constant 24-hour light or of normal 12-hour light/dark cycles. Stool samples were collected at the beginning and after the circadian rhythm disruption. A metatranscriptomic analysis revealed an increase in Ruminococcus torques, a bacterial species known to decrease gut barrier integrity, and a decrease in Lactobacillus johnsonii, a bacterium that helps maintain the intestinal epithelial cell layer, after circadian rhythm disruption. In addition, genes involved in pathways promoting host beneficial immune responses were downregulated, while genes involved in the synthesis and transportation of the endotoxin lipopolysaccharide were upregulated in mice with disrupted circadian cycles. Importantly, these mice were also more prone to dysfunction of the intestinal barrier. These results further elucidate the impact of light-cycle disruption on the gut microbiome and its connection with increased incidence of disease in response to circadian rhythm disturbances.